DRAINAGE SYSTEM DESIGN BASED ON ECO DRAINAGE CONCEPT AS AN EFFORT FOR WATER CONSERVATION AT THE MAIN CAMPUS OF INDONESIA UNIVERSITY OF EDUCATION - Fatharani Nandini, Mazaya
Drainage is a system built to deal with the problem of excess water either above the surface or below the surface. The North Bandung area is one of the areas that has an important role in ensuring the sustainability of life in the Bandung Basin. Currently, the North Bandung area is experiencing rapid development and conversion of green land into built-up land. The occurrence of land use change can cause rainwater runoff to increase so that it can increase runoff water and the risk of flooding downstream. The Main Campus of Indonesia Unniversity of Education is one of the state universities included in the North Bandung area so that a drainage system can be developed with the concept of eco drainage as an effort to reduce the potential for flooding downstream and add sustainability value to the system with a note that the application of the technology can be carried out in a drainage system that is separated from wastewater system. Hydrological analysis is the basis to calculate the existing conditions of drainage system. The result of hydrological analysis is the formation of an IDF curve generated using the Van Breen-Talbot Method. The determination of plan discharge as well as runoff discharge is carried out using the Rational Method. Design limitations, existing land conditions, topographic conditions, and soil conditions are things that are considered in determining the selected eco drainage technology, namely green roof and wetpond. There are five buildings that can be applied for green roof technology and two wetpond that can be applied at the Main Campus of the Indonesia University of Education. The application of those two technologies is able to provide a reduction in runoff discharge up to 54%. Total cost for implementation of eco drainage technologies in Indonesia University of Eduaction is Rp4,056,091,058.84 with the result of benefit cost ratio is 1,25 which states the project is feasible to implement.